Tertiary breast reconstruction using a free contralateral latissimus dorsi myocutaneous flap and contralateral internal mammary recipient vessel anastomosis. (March 2016) - Satake, Toshihiko; Muto, Mayu; Yasuoka, Yuji; Tamanoi, Yoshihiko; Hishikawa, Miki; Sugawara, Jun; Yasumura, Kazunori; Kobayashi, Shinji; Maegawa, Jiro
Abstract: Tertiary breast reconstruction after a failed autologous procedure is often performed under various restrictions, posing considerable problems not only in the choice of alternative free flap but also in that of recipient vessels. This is a case report of a free contralateral latissimus dorsi myocutaneous flap combined with a silicone gel implant, with flap pedicle anastomosis to the contralateral internal mammary recipient vessels in a 46-year-old woman with right breast deformity. She underwent a right modified radical mastectomy and failed attempts of reconstruction at another hospital. The deep inferior epigastric artery perforator flap had already been harvested for the failed reconstruction and high-level interruptions of the internal mammary, thoracodorsal, and thoracoacromial vessels were revealed on preoperative three-dimensional computed tomography angiography; therefore, we selected a contralateral latissimus dorsi myocutaneous flap to supply the lower pole skin along with a silicone gel implant for volume in this tertiary breast reconstruction. However, weak blood flow in the ipsilateral internal mammary artery and exhaustion of all recipient ipsilateral vessels in previous attempts to salvage the failing deep inferior epigastric artery perforator flap necessitated the use of the contralateral internal mammary recipient vessels. A contralateral latissimus dorsi myocutaneous flap with contralateral internal mammary recipient vessel anastomosis appears to be a viable option in complicated cases with unavailable deep inferior epigastric artery perforator flap or ipsilateral recipient vessels.